'Appeasing the Unstrung Mental Faculties': Listening to Music in Nineteenth-Century Lunatic Asylums. Issue 3 (18th December 2020) - Golding, Rosemary
Abstract : Listening to music found a new context during the early nineteenth century, in the shape of large, closed institutions set up to house and treat the insane. In response to social reform as well as a growing problem of mental health, lunatic asylums for paupers were set up across Britain during the first half of the nineteenth century. Replacing the previous practices of restraint and containment, a system of 'moral management' dominated the new asylums. Patients' lives were kept busy and ordered, with careful attention given to their employment, their diet and their recreational activities. Music played an important part in establishing the routine of the new institutions. Formal dances offered a social occasion and a controlled environment within which the two sexes could meet. Both dances and concerts were used as a reward for patient behaviour, encouraging the kind of self-control which was seen as crucial to recovery and rehabilitation. Musical events acted as a diversion from the grim realities of institutional life and played an important role in allowing patients to engage with religious observance. Musical experience could be active or passive; patients might engage by dancing or making music of their own, and their music might be symptomatic of illness or wellbeing. Using documents including formal records, patient notes and newspaper reports, it is possible to investigate some of the ways in which listening to music played a therapeutic role, and the place of musical experience in the lives of asylum patients.